Load type catalyst with low noble metal content as well as preparation method and application of load type catalyst
By uniformly distributing Pt, W, Group IIA elements and iron-based elements on the support, the problem of high Pt content in existing catalysts is solved, cost is reduced and reaction performance is maintained, and industrial application prospects are provided.
Patent Information
- Application Number
- CN202311271255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-28
AI Technical Summary
The Pt content in the existing propane dehydrogenation catalysts is high, resulting in high cost, high toxicity and unstable activity, which limits the development of the propane dehydrogenation process.
The low-precious metal content supported catalyst is used to uniformly distribute Pt, W, IIA elements and iron-based elements on the support, and the Pt content in the catalyst is reduced, and the uniformity and interaction of the active components are improved by coating method.
The loading of precious metal Pt in the catalyst is reduced, the cost of the catalyst is reduced, and the good alkane dehydrogenation reaction performance is maintained, with industrial application prospects.
Smart Images

Figure BDA0004475619290000091 
Figure BDA0004475619290000092 
Figure BDA0004475619290000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and more specifically to a low-noble metal content supported catalyst and a preparation method and application thereof. Background Art
[0002] As an important petrochemical raw material, propylene has become the second largest chemical monomer in demand after ethylene. Its main use is to produce chemical products such as polypropylene, acrylonitrile, and isopropanol. In recent years, the growth rate of global demand for propylene has far exceeded that of ethylene. Therefore, the world may face a shortage of propylene resources in the future. The traditional method of preparing propylene is to use ethylene co-production and cracking process of naphtha and light diesel. Expanding the production process of propylene sources has become a research focus in the field of petrochemicals. my country has abundant oil and natural gas resources, which contain a large amount of propane, but they are generally used as fuel or vented and burned, which wastes a lot of resources. How to produce high-value-added propylene that is in short supply in the market through catalytic dehydrogenation reaction of a large amount of cheap propane has significant economic and social benefits. Therefore, the method of preparing corresponding propylene through direct dehydrogenation process using propane in petrochemical by-products or natural gas as raw materials has received attention in recent years.
[0003] Propane dehydrogenation to propylene technology The industrialized or successfully developed propane catalytic dehydrogenation technologies include UOP's Oleflex process, CB&I Lummus's Catofin process, Snamprogetti-Yarsintez's fluidized bed FBD process, Krupp-Uhde's steam activated reforming STAR process, and Linde-BASF's PDH process. Currently, the most industrialized production processes are mainly UOP's Oleflex process in the United States, which uses Pt / Al2O3 catalysts, and CB&I Lummus's Catofin process in the United States, which uses Cr / Al2O3 catalysts. Both catalysts will be severely deactivated due to carbon deposition, and the catalysts need to be regenerated. In addition, chromium is toxic and unfavorable to the environment. The high price of platinum has seriously restricted the development of propane dehydrogenation technology. Therefore, it is of great practical significance to find a cheap, low-toxic, highly active and stable propane dehydrogenation catalyst.
[0004] Reducing the Pt content or Cr content in the catalyst is an important direction for improving the alkane dehydrogenation catalyst, but current research mainly focuses on the optimization of Pt-based catalysts, and there is little research on reducing the Pt content in the catalyst. The Pt content in the catalyst is generally above 0.3wt%. For example, U.S. Patents US3843560, US3903191, US3531544, US3647719, US4000210, US4046715, US4133842 describe alkane dehydrogenation catalysts that are Pt-Sn bimetallic systems, with alkali metals as acidity regulators, and a Pt loading of about 0.5%.
[0005] Therefore, how to reduce the Pt content in the alkane dehydrogenation catalyst while maintaining the catalytic performance thereof is a technical problem that needs to be solved. Summary of the invention
[0006] The object of the present invention is to provide a low-noble metal content supported catalyst and a preparation method and application thereof, so as to solve the technical problem of high Pt content in alkane dehydrogenation catalysts in the prior art.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] In the first aspect, the present invention provides a low-precious metal content supported catalyst, comprising: a) Pt or its oxide, b) W or its oxide, c) Group IIA element or its oxide, d) iron-based element or its oxide and e) a carrier; the mass ratio of the components is a:b:c:d:e=(0.01~0.3):(0.01~3):(0.01~1):(0.01~3):(95~99).
[0009] The low-noble metal content supported catalyst provided by the present invention adopts Pt as a dehydrogenation active component and uses W element, IIA group element and iron series element to strengthen the effect of Pt, so as to reduce the content of Pt in the catalyst and has good catalytic activity in the alkane dehydrogenation to olefin reaction.
[0010] In the present invention, the mass ratio of each component is calculated, the mass of Pt or its oxide is calculated as the mass of Pt; the mass of Cr or its oxide is calculated as the mass of Cr; the mass of Ge or its oxide is calculated as the mass of Ge; the mass of iron-based elements or their oxides is calculated as the mass of iron-based elements.
[0011] According to some embodiments of the present invention, the mass ratio of the components is a:b:c:d:e=(0.01-0.2):(0.1-2):(0.1-0.8):(0.1-2):(95-99).
[0012] According to some embodiments of the present invention, the mass ratio of the components is a:b:c:d:e=(0.05-0.2):(0.5-2):(0.1-0.8):(0.5-2):(95-99).
[0013] According to some embodiments of the present invention, the mass ratio of the components is a:b:c:d:e=(0.05-0.15):(1-2):(0.4-0.8):(0.5-2):(95-99).
[0014] According to some embodiments of the present invention, the surface area of Pt accounts for 0.5-1.0% of the total surface area of the catalyst.
[0015] In the present invention, the surface area of Pt refers to the area occupied by Pt on the catalyst surface.
[0016] According to some embodiments of the present invention, the support includes ZnAl2O4 composite oxide.
[0017] According to some embodiments of the present invention, the preparation method of the ZnAl2O4 composite oxide includes: preparing a solution including a soluble salt of Zn and a soluble salt of Al, dripping ammonia water under stirring conditions until the pH value is 7-9, aging, filtering, drying, and calcining to obtain the ZnAl2O4 composite oxide.
[0018] For catalysts used for dehydrogenation of alkanes to olefins, the acid centers on the surface of the catalyst carrier also undergo many side reactions, such as cracking and isomerization of alkanes and cracking, isomerization, and polymerization of olefins. Compared with common single carriers such as Al2O3, the catalyst provided by the present invention uses a composite oxide ZnAl2O4 as a carrier, which is beneficial to improving the stability of the catalytic reaction.
[0019] According to some embodiments of the invention, the Group IIA element includes at least one of Mg, Ca or Sr.
[0020] According to some embodiments of the present invention, the iron-based element includes at least one of Fe, Co or Ni.
[0021] In a second aspect, the present invention provides a method for preparing the catalyst described in the first aspect, comprising: mixing a solution including a soluble salt of Pt, a soluble salt of W, a soluble salt of a Group IIA element and a soluble salt of an iron-based element with a carrier, drying, and calcining to obtain the catalyst.
[0022] According to some embodiments of the present invention, the preparation method includes: first mixing a first solution including a soluble salt of a Group IIA element with a carrier, and performing a first drying and a first calcination to obtain a catalyst precursor; then mixing a second solution including a soluble salt of Pt, a soluble salt of W, and a soluble salt of an iron-based element with the catalyst precursor, and performing a second drying and a second calcination to obtain the catalyst.
[0023] According to some embodiments of the present invention, mixing the second solution with the catalyst precursor includes: spraying the second solution onto the surface of the catalyst precursor by a coating method.
[0024] The coating method is generally used to coat drug tablets, pills, etc. with sugar coating, organic film coating and water-soluble film coating, which can be achieved by using a coating machine. In the present invention, the coating method is used in the process of the carrier loading the active component, and the active component solution is atomized by the atomizer in the coating machine and then uniformly coated on the carrier surface, and quickly dried at high temperature to ensure the uniformity of the dispersion of each active component on the carrier surface, strengthen the interaction between the active components, and thus improve the performance of the catalyst.
[0025] According to some embodiments of the present invention, the coating method uses a coating machine, and the parameters of the coating machine are set as follows: main engine speed 10-30 rpm, fan speed 1000-2000 rpm, heating box temperature 100-200°C, solution feed rate 3-5 mL / min. The parameters of the coating machine are set within the above range, so that the impregnation liquid can be quickly dried and deposited on the carrier after contacting the carrier, ensuring the amount and uniformity of the impregnation, and minimizing the loss of the catalyst component.
[0026] According to some embodiments of the present invention, the temperature of the first drying is 80 to 150° C., and the time is 6 to 24 hours.
[0027] According to some embodiments of the present invention, the temperature of the first calcination is 450-750° C., and the time is 6-24 hours.
[0028] According to some embodiments of the present invention, the temperature of the second drying is 80 to 150° C., and the time is 6 to 24 hours.
[0029] According to some embodiments of the present invention, the temperature of the second calcination is 450-750° C., and the time is 6-24 hours.
[0030] In a third aspect, the present invention provides use of the catalyst described in the first aspect in dehydrogenation of alkanes to produce olefins.
[0031] According to some embodiments of the invention, the alkane is propane.
[0032] According to some embodiments of the present invention, the reaction conditions for the dehydrogenation of alkanes to olefins are: a volume ratio of water vapor to propane of (10-1):1, a reaction temperature of 400-600°C, a reaction pressure of 0-1 MPa, and an alkane mass space velocity of 3.0-8.0 h -1 .
[0033] The beneficial effects of the present invention are at least:
[0034] The low-noble metal content supported catalyst provided by the present invention reduces the loading amount of the noble metal Pt, thereby reducing the catalyst cost; at the same time, it maintains good alkane dehydrogenation reaction performance and has industrial application prospects. DETAILED DESCRIPTION
[0035] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this patent in detail and do not limit the scope of protection of the present invention in any way.
[0036] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the reagent amounts, unless otherwise specified, are the reagent amounts used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.
[0037] Preparation Example
[0038] Weigh 297.49g of zinc nitrate hexahydrate and 750.26g of aluminum nitrate nonahydrate and dissolve them in 1L of deionized water. Mix well, slowly add ammonia water under continuous stirring, adjust the pH value to 7.7, age the product for 2 hours, filter and wash the filter cake with 4L of water, dry the filter cake at 110°C for 16 hours, and calcine it in a muffle furnace at 680°C for 15 hours to obtain a ZnAl2O4 carrier.
[0039] Example 1
[0040] 8.44 g of magnesium nitrate hexahydrate was weighed and dissolved in 100 mL of water, 96.58 g of the ZnAl2O4 carrier of the preparation example was added under stirring, dried at 110° C. for 16 hours, and calcined in a muffle furnace at 680° C. for 15 hours to obtain a catalyst precursor; 0.32 g of chloroplatinic acid hexahydrate, 7.23 g of ferric nitrate nonahydrate and 2.01 g of ammonium metatungstate were weighed and dissolved in 100 mL of water; the solution was sprayed into the catalyst precursor using a Labcouting IV type high-efficiency coating machine, and the steps of spraying the solution were as follows: pouring the catalyst precursor into a rotating drum; setting the main engine speed to 20 rpm, the fan speed to 1500 rpm, and the heating box temperature to 180° C.; when the material temperature reached 50° C., the solution feed rate was set to 5 mL / min; after spraying, the coating machine continued to run for 30 min, the catalyst precursor sprayed with the solution was taken out, dried at 110° C. for 16 hours, and calcined in a muffle furnace at 680° C. for 15 hours to obtain a catalyst.
[0041] Example 2
[0042] 8.44 g of magnesium nitrate hexahydrate was weighed and dissolved in 100 mL of water, 95.12 g of the ZnAl2O4 carrier of the preparation example was added under stirring, dried at 110° C. for 16 hours, and calcined in a muffle furnace at 680° C. for 15 hours to obtain a catalyst precursor; 0.213 g of chloroplatinic acid hexahydrate, 14.46 g of ferric nitrate nonahydrate and 2.68 g of ammonium metatungstate were weighed and dissolved in 100 mL of water; the solution was sprayed into the catalyst precursor using a Labcouting IV type high-efficiency coating machine, and the steps of spraying the solution were as follows: pouring the catalyst precursor into a rotating drum; setting the main engine speed to 15 rpm, the fan speed to 2000 rpm, and the heating box temperature to 180° C.; when the material temperature reached 50° C., the solution feed rate was set to 4 mL / min; after spraying, the coating machine continued to run for 30 min, the catalyst precursor sprayed with the solution was taken out, dried at 110° C. for 16 hours, and calcined in a muffle furnace at 680° C. for 15 hours to obtain a catalyst.
[0043] Example 3
[0044] The preparation method of the catalyst is the same as that of Example 1, except that 8.44 g of magnesium nitrate hexahydrate is replaced by 4.71 g of calcium nitrate tetrahydrate.
[0045] Example 4
[0046] The preparation method of the catalyst is the same as that of Example 1, except that 8.44 g of magnesium nitrate hexahydrate is replaced by 1.93 g of strontium nitrate.
[0047] Example 5
[0048] The preparation method of the catalyst is similar to that of Example 1, except that 7.23 g of ferric nitrate nonahydrate is replaced by 4.94 g of cobalt nitrate hexahydrate.
[0049] Example 6
[0050] The preparation method of the catalyst is similar to that of Example 1, except that 7.23 g of ferric nitrate nonahydrate is replaced by 4.96 g of nickel nitrate hexahydrate.
[0051] Example 7
[0052] Weigh 8.44g of magnesium nitrate hexahydrate, 0.32g of chloroplatinic acid hexahydrate, 7.23g of ferric nitrate nonahydrate and 2.01g of ammonium metatungstate and dissolve them in 100mL of water; spray the solution into 96.58g of the ZnAl2O4 carrier of the preparation example using a Labcouting IV type high-efficiency coating machine, and the steps of spraying the solution are as follows: pour the ZnAl2O4 carrier into a rotating drum; set the main engine speed to 20 rpm, the fan speed to 1500 rpm, and the heating box temperature to 180°C; when the material temperature reaches 50°C, the solution feed rate is set to 5mL / min; after spraying, the coating machine continues to run for 30min, take out the ZnAl2O4 carrier sprayed with the solution, dry it at 110°C for 16 hours, and calcine it in a muffle furnace at 680°C for 15 hours to obtain a catalyst.
[0053] Example 8
[0054] Weigh 8.44g of magnesium nitrate hexahydrate and dissolve it in 100mL of water, add 96.58g of the ZnAl2O4 carrier of the preparation example under stirring, dry at 110°C for 16 hours, and calcine in a muffle furnace at 680°C for 15 hours to obtain a catalyst precursor; weigh 0.32g of chloroplatinic acid hexahydrate, 7.23g of ferric nitrate nonahydrate and 2.01g of ammonium metatungstate and dissolve them in 100mL of water, add the catalyst precursor under stirring, dry at 110°C for 16 hours, and calcine in a muffle furnace at 680°C for 15 hours to obtain a catalyst.
[0055] Comparative Example 1
[0056] Weigh 0.32 g of chloroplatinic acid hexahydrate and dissolve it in 100 mL of water. Add it to 99.88 g of the ZnAl2O4 carrier of the preparation example while stirring, mix well, let it stand for 2 hours, dry it at 110°C for 16 hours, and calcine it in a muffle furnace at 680°C for 15 hours to obtain the catalyst.
[0057] Comparative Example 2
[0058] The preparation method of the catalyst refers to Example 1, except that: 2.01 g of ammonium metatungstate is not added, and the addition amount of the ZnAl2O4 carrier is 98.08 g.
[0059] Comparative Example 3
[0060] Weigh 0.32g of chloroplatinic acid hexahydrate, 7.23g of ferric nitrate nonahydrate and 2.01g of ammonium metatungstate and dissolve them in 100mL of water; spray the solution into 97.38g of the ZnAl2O4 carrier of the preparation example using a Labcouting IV high-efficiency coating machine, and the steps of spraying the solution are as follows: pour the ZnAl2O4 carrier into a rotating drum; set the main engine speed to 20 rpm, the fan speed to 1500 rpm, and the heating box temperature to 180°C; when the material temperature reaches 50°C, the solution feed rate is set to 5mL / min; after spraying, the coating machine continues to run for 30min, take out the ZnAl2O4 carrier sprayed with the solution, dry it at 110°C for 16 hours, and calcine it in a muffle furnace at 680°C for 15 hours to obtain a catalyst.
[0061] Comparative Example 4
[0062] The preparation method of the catalyst refers to Example 1, except that: 7.23 g of ferric nitrate nonahydrate is not added, and the addition amount of the ZnAl2O4 carrier is 97.58 g.
[0063] Catalyst performance evaluation
[0064] (1) Catalyst activity evaluation
[0065] The catalysts prepared in the examples and comparative examples were evaluated for catalyst activity in an isothermal fixed bed reactor. The evaluation method is as follows:
[0066] The propane gas is adjusted by mass flow meter, enters the preheating zone for mixing, and then enters the reaction zone. The preheating zone and reaction zone of the reactor are heated by electric heating wire to reach the predetermined temperature. The inner diameter of the reactor is a stainless steel sleeve with a length of about 400mm and a diameter of 9mm-6mm. The reacted gas passes through the condenser and enters the gas chromatograph to analyze its composition.
[0067] Evaluation criteria include:
[0068] 0.5 g of catalyst was loaded into the above isothermal fixed bed reactor (catalyst bed height 17 mm), atmospheric pressure, temperature 560 ° C; the volume ratio of water vapor to propane was 8:1; the propane mass space velocity was 3.0 h -1 .
[0069] The propane conversion and propylene selectivity are calculated as follows:
[0070]
[0071]
[0072] The contents of substances in the above calculation formulas are all molar amounts.
[0073] The evaluation results are shown in Table 1.
[0074] (2) Surface area of Pt on the catalyst:
[0075] The temperature was raised to 550°C at 10°C / min, and then reduced with H2 / Ar for 2h. The temperature was then changed to 580°C with Ar atmosphere, purged for 1h, and cooled to 45°C. Pure H2 was used for 3min pulses until adsorption equilibrium was reached. The system was adjusted according to the H2 pulse adsorption capacity V H (mL, STP), assuming that the ratio of metal Pt to H2 adsorbed atoms is 1:1, the surface area of metal Pt on the catalyst S Pt (m 2 The calculation formula of γ / g is as follows:
[0076]
[0077] Where V H (mL, STP) represents the total volume of H2 consumed by the sample; N0 is Avogadro’s constant 6.019×10 23 ; σ is the cross-sectional area of the Pt atom 0.089 nm, W is the mass of the catalyst sample (g); P is the mass fraction of Pt in the catalyst (%).
[0078] (3) Catalyst surface area:
[0079] The N2 physical adsorption method was used for determination, using the ASAP2010 rapid specific surface pore size distribution measuring instrument from Micromeritics Inc., USA. Before the sample measurement, 0.1 g of the sample was first vacuum degassed at 300°C for more than 5 hours, and then a N2 adsorption-desorption experiment was performed at liquid nitrogen temperature to obtain the adsorption-desorption curve. The catalyst surface area was calculated using the Brunauer-Emmet-Teller (BET) method.
[0080] Table 1
[0081]
[0082]
[0083] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A low noble metal content supported catalyst, characterized in that: include: a) Pt or its oxide, b) W or its oxide, c) Group IIA element or its oxide, d) iron-based element or its oxide and e) carrier; the mass ratio of the components is a:b:c:d:e=(0.01-0.3):(0.01-3):(0.01-1):(0.01-3):(95-99).
2. The catalyst according to claim 1, characterized in that The mass ratio of the components is a:b:c:d:e=(0.01-0.2):(0.1-2):(0.1-0.8):(0.1-2):(95-99).
3. The catalyst according to claim 1 or 2, characterized in that The ratio of the surface area of Pt to the total surface area of the catalyst is 0.5-1.0%.
4. The catalyst according to any one of claims 1 to 3, characterized in that The carrier comprises ZnAl2O4 composite oxide; and / or, the Group IIA element includes at least one of Mg, Ca or Sr; And / or, the iron-based element includes at least one of Fe, Co or Ni.
5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: include: The catalyst is prepared by mixing a solution including a soluble salt of Pt, a soluble salt of W, a soluble salt of a Group IIA element and a soluble salt of an iron series element with a carrier, drying and calcining the mixture.
6. The preparation method according to claim 5, characterized in that: The preparation method comprises: firstly mixing a first solution including soluble salts of group IIA elements with a carrier, performing a first drying and a first calcination to obtain a catalyst precursor; then mixing a second solution including soluble salts of Pt, soluble salts of W and soluble salts of iron-based elements with the catalyst precursor, performing a second drying and a second calcination to obtain the catalyst.
7. The preparation method according to claim 6, characterized in that: The mixing of the second solution with the catalyst precursor comprises: spraying the second solution onto the surface of the catalyst precursor by a coating method.
8. The preparation method according to claim 7, characterized in that: The coating method adopts a coating machine, and the parameters of the coating machine are set as follows: main engine speed 10-30 rpm, fan speed 1000-2000 rpm, heating box temperature 100-200°C, and solution feed rate 3-5 mL / min.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The temperature of the first drying is 80-150°C; And / or, the first calcination temperature is 450-750° C. and the time is 6-24 hours; And / or, the temperature of the second drying is 80-150°C; And / or, the temperature of the second calcination is 450-750° C., and the time is 6-24 hours.
10. Use of the catalyst according to any one of claims 1 to 4 in dehydrogenation of alkanes to olefins.
Citation Information
Patent Citations
Selective dehydrogenation of long-chain normal paraffin hydrocarbons
US3531544A
Dehydrogenation method and catalytic composite for use therein
US3647719A
Multicomponent dehydrogenation catalyst containing platinum,iridium,alkali or alkaline earth metal oxide,and sulfur
US3843560A
Dehydrogenation of normal paraffins to obtain normal mono-olefins
US3903191A
Selective dehydrogenation of n-paraffins to n-olefins
US4000210A